Análisis, diseño y construcción de un simulador de señales de paciente para ser usado en electrocardiografía, utilizando comandos digitales - Yapur, Miguel (2010)
The purpose of this project is the design and construction of a simulator that generates signals similar to those produced by the heart; these are captured and registered by the electrocardiograph. This project use the PIC16F886, a mid-range microcontroller, programmed in C language using the compiler PICC of CCS enterprises. The circuit, besides simulating a normal cardiac signal, can also generate pathologies such as arrhythmia, tachycardia and bradycardia;, also can vary manually the increase or decrease of the heart rate in steps of 10 beats per minute(bpm). The number of beats per minute generated by the device, can be seen through 3 7-segment displays. This project was conceived by the need of designing a device that can be user-friendly and accessible; so in the present work a cheap circuit is implemented, avoiding the waste of resources and using more efficient designing techniques